Mesenchymal Stem Cell-Derived Exosomal MiRNAs Promote M2 Macrophages Polarization: Therapeutic Opportunities for Spinal Cord Injury - Liang, Ze-Yan; Xu, Xiong-Jie; Rao, Jian; Yang, Zhe-Lun; Wang, Chun-Hua; Chen, Chun-Mei (Frontiers in Molecular Neuroscience, 2022)
Spinal cord injury (SCI) is an enormous public health concern affecting approximately 250,000–500,000 people worldwide each year. It is mostly irreversible considering the limitations of currently available treatments, and its prevention and management have been the prime focus of many studies. Mesenchymal stem cell (MSC) transplantation is one of the most promising treatments for SCI. The role of MSCs in SCI has been studied extensively, and MSCs have been shown to have many limitations. Moreover, the therapeutic effects of MSCs are more likely related to paracrine effects. In SCIs, macrophages from peripheral sources differentiate into M1 macrophages, promoting inflammation and aggravating neuronal damage; however, studies have shown that MSC-derived exosomes can induce the polarization of macrophages from the M1 to the M2 phenotype, thereby promoting nerve function recovery in patients with SCI. In this review, we discussed the research progress of MSC-derived exosomal miRNAs in promoting M2 macrophage differentiation in the SCI, and introduced some exosomal miRNAs that can regulate the differentiation of M2 macrophages in non-SCI; it is hoped that the regulatory role of these exosome-derived miRNAs can be confirmed in SCI.